The Recent Past and Possible Futures of Citizen Science: Final Remarks - Josep Perelló; Andrzej Klimczuk; Anne Land-Zandstra; Katrin Vohland; Katherin Wagenknecht; Claire Narraway; Rob Lemmens; Marisa Ponti (The Science of Citizen Science, 2021)
This book is the culmination of the COST Action CA15212 Citizen Science to Promote Creativity, Scientific Literacy, and Innovation throughout Europe. It represents the final stage of a shared journey taken over the last 4 years. During this relatively short period, our citizen science practices and perspectives have rapidly evolved. In this chapter we discuss what we have learnt about the recent past of citizen science and what we expect and hope for the future.
Keywords: D83; D89; Z00; 330; Citizen Science; Possible Futures of Citizen Science; Funding and Citizen Science; Public Policy and Citizen Science; Project Management and Organisation; Scientific Impact; Public Participation; Scientific Literacy